Global biomes for the Last Interglacial period (127-119 ka) simulated by BIOME4 using CESM2-CISM2 coupled climate–ice sheet model data - Shafer, Sarah; Bartlein, Patrick J; Sommers, Aleah N; Otto-Bliesner, Bette L; Lipscomb, William H; Lofverstrom, Marcus; Brady, Esther C; Kluzek, Erik; Leguy, Gunter; Thayer-Calder, Katherine; Tomas, Robert A (U.S. Geological Survey, 2021)
This data release contains: 1) the BIOME4-simulated biome data used to create Sommers et al. (2021) Figures 2, 6, S6, and S7; 2) the CESM2-CISM2 calendar-adjusted temperature data used to create Sommers et al. (2021) Figures 2, 7, S2-S5, and S8-S11; and 3) land, ice, and ocean mask data and continent and ice sheet outline files. Additional CESM2-CISM2 simulation data described in Sommers et al. (2021) are available from the University Corporation for Atmospheric Research (UCAR)/National Center for Atmospheric Research (NCAR) Digital Asset Services Hub (DASH; https://doi.org/10.5065/as0j-6387). The simulated biome data are on a global 0.5-degree grid for the Last Interglacial (LIG; 127.0-119.0 ka) at 500-year time steps (i.e., 127.0 ka, 126.5 ka, …, 119.0 ka). Biomes were simulated with BIOME4 (ver. 4.2b2; Kaplan et al. 2003; https://pmip2.lsce.ipsl.fr/synth/biome4.shtml), an equilibrium vegetation model, using CESM2 (version 2.1.0)-simulated climate data produced under the PMIP4/CMIP6 (Paleoclimate Modelling Intercomparison Project phase 4 / Coupled Model Intercomparison Project phase 6) “lig127k” experiment (Otto-Bliesner et al. 2017, 2020). For the CESM2 simulations from 127.0 through 119.0 ka, CESM2 was coupled with the land ice model CISM2 (version 2.1) to simulate changes in the Greenland Ice Sheet (GrIS; Sommers et al. 2021). Output from this simulation was saved at 500-yr intervals and used as input to BIOME4. The climate data (temperature, precipitation, and cloud cover) were regridded to a 0.5-degree global grid, calendar adjusted using PaleoCalAdjust v1.0 (Bartlein and Shafer 2019), and bias corrected using long-term mean differences applied to CRU CL 2.0 (1961-1990 30-year mean) climate data (New et al. 2002). Ice mask data are described in Section 3 in the readme file. See Sommers et al. (2021) for additional details regarding the methods used to create the biome data. Sommers et al. (2021) describe two different CESM2-CISM2 LIG simulations that use different landcover vegetation, one using BIOME4-simulated vegetation (“BIOME4 veg”; 127.0-119.0 ka) and the other using pre-industrial vegetation assuming no anthropogenic influence (“no-Anthro veg”; 126.5-121.0 ka). Calendar-adjusted near-surface air temperature data on the CESM2 grid from these two simulations are described in Sections 2.1 and 2.2 in the readme file. These temperature data were used in Sommers et al. (2021) Figures 2, 7, S2-S5, and S8-S11. The data included in this data release were developed for climate-related research and may not be suitable for other applications. Note that the data may require masking before use (see Section 3 in the readme file). The data are provided in self-documenting netCDF (network Common Data Form) files (Unidata 2011). References Bartlein, P.J., and Shafer, S.L., 2019, Paleo calendar-effect adjustments in time-slice and transient climate-model simulations (PaleoCalAdjust v1.0): impact and strategies for data analysis: Geoscientific Model Development 12, 3889-3913, https://doi.org/10.5194/gmd-12-3889-2019. Harrison, S.P., 2017, BIOME 6000 DB classified plotfile version 1: University of Reading. Dataset, http://dx.doi.org/10.17864/1947.99. Kaplan, J.O., Bigelow, N.H., Prentice, I.C., Harrison, S.P., Bartlein, P.J., Christensen, T.R., et al., 2003, Climate change and Arctic ecosystems: 2. Modeling, paleodata-model comparisons, and future projections: Journal of Geophysical Research: Atmospheres 108(D19), 8171, https://doi.org/10.1029/2002JD002559. New, M., Lister, D., Hulme, M., and Makin, I., 2002, A high-resolution data set of surface climate over global land areas: Climate Research 21, 1-25, https://doi.org/10.3354/cr021001. Otto-Bliesner, B.L., Braconnot, P., Harrison, S.P., Lunt, D.J., Abe-Ouchi, A., Albani, S., et al., 2017, The PMIP4 contribution to CMIP6 – Part 2: Two interglacials, scientific objective and experimental design for Holocene and Last Interglacial simulations: Geoscientific Model Development 10, 3979-4003, https://doi.org/10.5194/gmd-10-3979-2017. Otto-Bliesner, B.L., Brady, E.C., Tomas, R.A., Albani, S., Bartlein, P.J., Mahowald, N.M., et al., 2020, A comparison of the CMIP6 midHolocene and lig127k simulations in CESM2: Paleoceanography and Paleoclimatology 35, e2020PA003957, https://doi.org/10.1029/2020PA003957. Shafer, S.L., Bartlein, P.J., Otto-Bliesner, B.L., Brady, E.C., 2020, Biomes simulated by BIOME4 using CESM2 lig127k, midHolocene, and piControl climate data on a global 0.5-degree grid: U.S. Geological Survey data release, https://doi.org/10.5066/P9D9S4EY. Sommers, A.N., Otto-Bliesner, B.L., Lipscomb, W.H., Lofverstrom, M., Shafer, S.L., Bartlein, P.J., et al., 2021, Retreat and regrowth of the Greenland Ice Sheet during the Last Interglacial as simulated by the CESM2-CISM2 coupled climate–ice sheet model: Paleoceanography and Paleoclimatology e2021PA004272, https://doi.org/10.1029/2021PA004272. Unidata, 2011, Network Common Data Form (netCDF) version 4.1.3 [software]: UCAR/Unidata, Boulder, Colorado, https://doi.org/10.5065/D6H70CW6.